BOZH AND DOVBUSH IN THE LIGHT OF CARPATHIANS LEGENDS - Pushyk, S. G. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article is an excerpt from a new book by an author who explores the Carpathian opryshky phenomenon through a system of folk and mythological rites and plots, including legends.